#BlackProtest from the web to the streets and back: Feminist digital activism in Poland and narrative potential of the hashtag. Issue 2 (May 2021) - Nacher, Anna
In this article, I would like to take a somewhat closer look at the politics of hashtags surrounding wave of street actions known as Black Protest (Czarny Protest), held nation-wide in Poland on October 2016. Analysing the use of social media as the form of digital activism, I strive at both mitigating the fallacy of digital dualism and demystifying the notion of 'Twitter revolutions'. The term was popularized by over-enthusiastic accounts of the social movements between 2009 and 2011. I propose to see the employment of social media platforms as the form of weak opposition and to some extent, to explain its efficiency by the ability to reclaim and mobilize the narrative power of hashtags. 'Weak' here means everyday, often mundane, and hence under-recognized acts as opposed to activity considered 'heroic' and placed in the spotlight, with all gender-based ideological and interpretative undercurrents associated with such a juxtaposition.